An Integrated Framework for Measuring Public Sector Performance at the Village Level: Insights from the Balanced Scorecard and AHP - Saipul Arni Muhsyaf; Adhitya Bayu Suryantara; ⁠Isnawati Isnawati; Husfan Riandi (Yayasan Ghalih Pelopor Pendidikan, 2025)
Measuing the performance of village governments in Indonesia remains a key challenge in ensuring accountable, effective, and citizen-oriented governance. This study aims to develop a contextual performance measurement model for Desa Teros in East Lombok by integrating the Balanced Scorecard (BSC) framework with the Analytical Hierarchy Process (AHP). The model incorporates four strategic perspectives, financial, customer (citizen), internal business processes, and learning and growth tailored to the village government context. Data were collected through interviews and structured questionnaires distributed to key stakeholders, including village officials and supervisory board members. AHP was employed to prioritize performance indicators across the BSC dimensions. Results indicate that the customer perspective holds the highest priority (weight: 0.463), highlighting the centrality of citizen satisfaction and public service quality in village-level performance. This is followed by the financial perspective (0.263), internal business processes (0.170), and learning and growth (0.104). The study contributes both theoretically and practically by presenting a strategic performance model specifically designed for rural governance, offering an adaptable framework for other villages with similar characteristics. The integrated BSC-AHP approach also supports data-driven decision-making and promotes transparency and participatory development planning at the grassroots level.